STUDENTS’ PERCEPTION OF THE PROJECT-BASED LEARNING MODEL USED BY ENGLISH TEACHERS AT ELEVENT GRADER OF SMA N 1 KECAMATAN KAPUR IX - Indah Rahmalia; Ifna Nifriza; Mawaddah Hadza (Ensiklopedia of Journal, 2025)
This study aims to explore the perceptions of eleventh-grade students at SMA Negeri 1 Kapur IX towards the project-based learning model used by their English teachers. This study was motivated by the need to determine students' perceptions towards the implementation of PjBL which has been implemented by English teachers at SMA N 1 Kapur IX. This study used a qualitative descriptive approach involving 191 students selected through purposive sampling technique. Data were collected through a questionnaire consisting of 30 statements with five answer choices, then analyzed using Sudijono's formula (2010) and categorized based on score intervals. The results of this study indicate that students' perceptions in the project-based learning model used by English teachers are in the good perceptions category with a score of 120.20. Data analysis shows that students' perceptions of project-based learning model in the student-centered perception indicator are in the good category with a score of 120.6, authentic problem-based perception is in the good category with a score of 121.6, in-depth inquiry perception is in the less enough category with a score of 114.8, then collaborative learning perception is in the very good category with a score of 129, tangible product perception is in the less enough category with a score of 114.4, and finally reflection and revision perception is in the good category with a score of 120.8. Keywords: Student Perceptions, Project-Based Learning, English Teachers.